Teachers’ Perception of the Implementation of Inclusive Education in PAUD Unit in Lamongan District - Nawafilaty, Tawaduddin (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Inclusive education is education that carries out learning for all children both normal childrenand children with special needs. It is intended that all children get proper education inaccordance with the law. The problem is still often found children who need special handlingwho have not received an education like a normal child. So this study aims to determine theteacher's opinion about the importance of implementing inclusive education in PAUD units and obtain results p = 0,000 (p <0.001), so it can be said that the hypothesis is accepted that there is a relationship between teacher perceptions and the implementation of inclusive PAUD in PAUD institutions in Lamongan Regency. The more teachers who support the implementation of inclusive PAUD in PAUD institutions in Lamongan district, the more opportunities to deal with children who have special needs